Increased expression of estrogen receptors at the materno-fetal interface in patients with recurrent pregnency loss (Iraqi Journal of Medical Sciences, 2009)
Background: Estrogen hormone has been implicated in the pathogenesis of different genital tract pathologies and in counteracting the progress of normal pregnancy.Objective: Localization and semi-quantization of estrogen receptors at the materno-fetal interface in patients with recurrent pregnancy loss (RPL).Methods: Immunohistochemistry analysis of estrogen receptors using paraffin embedded sections of curate samples obtained from 40 women, who where divided into three groups: 24 women with RPL, 10 women with abortion for the first time, and 6 women with induced abortion.Results: The mean value of the expression of estrogen receptors was (71.2 ± 2.3), which is significantly higher than that of the second group (52.2 ± 3.2), and the third group (43.7 ± 4.2), (p=0.001).Conclusion: High expression of estrogen receptors in women with RPL may give a clue to its prominent role in the pathology of pregnancy loss.Key wards: Estrogen receptor, RPL.